Out in the East - Patrick Farges (Mélanges de la Casa de Velázquez, 2020)
The history of contemporary Germany is a comparative horizon, if not a counterpoint, when considering the structuring of the public and private spheres in societies in a post-dictatorial context. Indeed, German reunification, marked by the fall of the Wall in 1989, paved the way for a redesign of the public and private sectors. Moreover, the gender and sexuality arrangements within the two Germanies (1949-1990) followed the Nazi obsession with sexuality and intimacy, instruments of a total and totalitarian control of the private sphere. To what extent did the GDR break with the Nazi heritage and put in place original arrangements for the history of gender and homosexuality? Based on a review of recent work in the history of sexuality in Germany, we will examine the possible (gay) sexualized territories in a dictatorial context, the strategies of deviation/resistance as well as the lived spaces (Lebenswelten) and the spaces of action (Handlungsräume) of queer actors before and after the fall of the wall. We will also consider the reconfigurations that have been taking place since reunification.